2007
DOI: 10.1111/j.1365-277x.2007.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc intake and sex differences in taste acuity in healthy young adults

Abstract: These findings suggest that zinc is more important for taste acuity in males than females and indicate the importance of taking sex differences into account when studying taste acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
4
21
0
3
Order By: Relevance
“…FFQ and 24 h recall), in agreement with our findings irrespective of the method of measurement (25,47) . Lower intakes of phytic acid, Zn and protein in women than in men as observed in our study have been reported previously by McDaid et al (48) , Amirabdollahian and Ash (27) , Coulibaly et al (49) and Adamson et al (47) . These differences may due to differences in energy intake between the age and gender groups; we observed that total energy intake was lower in older than in young adults and in female than male participants (data not shown).…”
Section: Effects Of Age and Gender On Intakes Of Zn And Zn-absorptionsupporting
confidence: 87%
“…FFQ and 24 h recall), in agreement with our findings irrespective of the method of measurement (25,47) . Lower intakes of phytic acid, Zn and protein in women than in men as observed in our study have been reported previously by McDaid et al (48) , Amirabdollahian and Ash (27) , Coulibaly et al (49) and Adamson et al (47) . These differences may due to differences in energy intake between the age and gender groups; we observed that total energy intake was lower in older than in young adults and in female than male participants (data not shown).…”
Section: Effects Of Age and Gender On Intakes Of Zn And Zn-absorptionsupporting
confidence: 87%
“…Higher dietary intakes of zinc were associated with better acuity for salt taste specifically in females [17]. Pluhator, and others [16] suggested taste preference will provide to be more reproducibly related to zinc nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…There would be two causes of zinc deficiency, one is low zinc intake and the other is high intake of processed and prepared foods with polyphosphoric acid sodium, which drain zinc from the body [17,18]. There are some possibilities to improve zinc deficiency by examining eating style factors considering these aspects.…”
Section: Introductionmentioning
confidence: 99%
“…O tempo de permanência da solução na boca antes de ser deglutida ou descartada foi relatado somente por dois estudos (ANTONELLO et al, 2007;SPRITZER, 1985), sendo ambos de 10 s. As amostras foram desprezadas em 27,3% dos artigos (ELLEGARD et al, 2007a;MONNEUSE et al, 2008;ZVEREV et al, 2004;PASQUET et al, 2002;MOJET et al, 2001; MIDDLETON; ALLMAN-FARINELLI, 1999) e deglutidas em 18,2% (STEWART-KNOX et al, 2008;GUDZIOL;HUMMEL, 2007;McDAID et al, 2007;OKORO et al, 2002); note-se, porém, que 54,5% não informaram. Quanto à duração do intervalo entre as soluções diferentes, em dois estudos (9,1%), foi de 30 s (ANTONELLO et al, 2007;SPRITZER, 1985); em um estudo (4,5%), de 3 min (WATANABE et al, 2008), e a maioria deles (86,4%) não relatou.…”
Section: Aspectos Gerais Dos Artigos Para Avaliação Sensorialunclassified
“…No entanto, apenas 13 (48,1%) dos 27 artigos fizeram recomendações para abstenções (STEWART-KNOX et al 2008;GUDZIOL;HUMMEL, 2007;McDAID et al, 2007;HEATH et al, 2006;HONG et al, 2005;SIENKIEWICZ-JAROSZ et al, 2005;UKOH et al, 2004;TUNSURIYAWONG et al, 2000;MIDDLETON;ALLMAN-FARINELLI, 1999;HORIO;KAWAMURA, 1998;OKORO et al, 2002;ANTONELLO et al, 2007;SPRITZER, 1985). As orientações feitas com maior frequência foram: evitar a ingestão de alimentos (48,1%) e não fumar (37%).…”
Section: Estímulo Localizadounclassified